STRATEGI PENGEMBANGAN USAHA MINUMAN HERBAL EUFRAINO DI KOTA MANADO (Development Strategy of EufrainoHerbal Drink Business in Manado City) - Diandra Z. Rambitan; Esry O.H. Laoh; Leonardus R. Rengkung (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2019)
The objective of this research is to identify internal and external factors that affect the to compile and recommend the right strategy alternative of Business Development Strategy of Eufraino Herbal Drink in facing competition. By using SWOT analysis such as theÂ IFE and EFE matrix can be identified as important factors from the internal environment and the external environment that become strengths, weaknesses, opportunities and threats of this business. Data analysis used in this study is a descriptive analysis.Â The process of formulating strategies to analyse those internal and external environments by the three stages namely, input stage, matching stage and decision stage. The analytical tools used to formulate such strategies are IFE and EFE matrix in input stage, I-E matrix, Grand Strategy matrix, and SWOT matrix in matching stage, and as QSPM at the decision stage. Research results showed that the priority of the business development strategy can be carried out was developing some new product innovations so that the consumers will not switch to another product..Keywords: Business Development Strategy - Eufraino Herbal Drink